Measurement of Aspheric Surfaces Using an Arcuate Region Scanning Method by 2D Laser Displacement Sensor. Issue 1 (1st January 2022) - Lan, Menghui; Li, Bing; Wei, Xiang; Wu, Xiuyuan
Abstract: This study proposes an effective measurement of aspheric surfaces using arcuate region scanning method by 2D laser displacement sensor. In a global coordinate system, the point cloud data of each arcuate region in aspheric surface are obtained successively, coordinated with the rotation of the rotating platform and the transverse movement of the 2D laser displacement sensor in a fixed step size. When scanning different areas, it is necessary to calculate the scanning angle gap and included angle according to different scanning length of arc. Then the aspheric surface error could be calculated through the reconstruction consequence. It can be used for in-situ measurement in the processing stage of aspheric mirrors. We present an experiment compared with the measurement results of PGI to verify the validity of this measurement method.